Revitalization of nipa thatch as sustainable roofing material at Sekolah Alam Balikpapan - Pratyaksa, Adhika Bayu; Barliana, Mokhamad Syaom; Permana, Asep Yudi (Center for Science and Technology, IAIN Surakarta, 2025)
Nipa as thatch roofing material originates from leaves of nipa palm tree (Nypa fruticans). Although nipa has a long history in Southeast Asia, it has gradually been replaced by other materials. Nature school (sekolah alam), a relatively new education model established in Indonesia in 1998, offer a different approach to school facilities, one of which is the use of open-air classroom buildings. Balikpapan Nature School, located in island of Borneo, is one of many institutions developing the nature-based school concept. The school has adopted the Dayak Kenyah longhouse design, incorporating nipa thatch roofing in its buildings. However, one of the buildings has had its nipa roofing replaced with bitumen. This research investigates the heat gain characteristics of nipa roofing as a sustainable material in comparison to bitumen roofing. Analysis of the observational data using paired t-test shows a significant difference, with nipa roofing effectively reducing heat gain. These supports findings support previous studies that have identified nipa as an environmentally friendly material capable of providing better thermal comfort in humid tropical climates.